Biology of Aging I. (11th November 2018) - Kane, A; Keller, K; Heinze-Milne, S; Grandy, S; Howlett, S
Abstract: A frailty index based on clinical deficit accumulation (FI-Clinical) quantifies frailty in aging mice. We aimed to develop a laboratory test-based murine FI tool (FI-Lab) and to investigate the effects of age and sex on FI-Lab scores, FI-Clinical scores and the combination (FI-Combined), as well as to explore links between frailty and inflammation. Studies used older (17 & 23-months) C57BL/6 mice of both sexes. We developed an FI-Lab (blood pressure, blood chemistry, echocardiography) based on deviation from reference values in younger adults (12 months), which showed similar characteristics to a human FI-Lab tool. Interestingly, while FI-Clinical scores were higher in females, the opposite was true for FI-Lab scores and there was no sex difference in FI-Combined scores. All three FI tools revealed a positive correlation between pro-inflammatory cytokine levels and frailty in aging mice that differed between the sexes. Elevated levels of the pro-inflammatory cytokines interleukin-6, interleukin-9 and interferon-γ were associated with higher FI scores in aging females, while levels of interleukin-12p40 rose as FI scores increased in older males. Thus, an FI tool based on common laboratory tests can quantify frailty in mice; the positive correlation between inflammation and frailty scores in naturally-aging mice differs between the sexes.